The economic impact of international sports organisations in Switzerland 2014-2019 - Stricker, C.; Derchi, G.-B. (AISTS, 2021)
Overall, the current study, which consolidates data from 53 International Sports Organisations that had a physical presence in Switzerland during the years 2014 to 2019, shows that the value created by these organisations corresponds to an increased growth in their economic impact of 57 per cent for the whole of Switzerland, compared to the previous period of 2008 to 2013.